Un autre point de vue sur have - Catherine Douay (Corela)
Grammaticalized uses of have in perfect tenses or in constructions such as have to+V and have a + V (have a drink, a look) point to a core meaning of this verb as a relational marker. Neither aspect- nor modality-based explanations seem adequate as they fail to provide a unified account of attested occurrences. In particular, emphasis on speakers’ “viewpoints” should be reassessed. In the framework of our own study of the formal conditions of interlocution, we argue that the role of have is precisely to avoid any reference to any viewpoint.